Software Engineering: Challenges and Solutions Results of the XVIII KKIO 2016 Software Engineering Conference 2016 held at September 15-17 2016 in Wroclaw, Poland - Madeyski, Lech.; Śmiałek, Michał; Hnatkowska, Bogumiła; Huzar, Zbigniev; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the proceedings of the KKIO Software Engineering Conference held in Wrocław, Poland in September 15-17, 2016. It contains the carefully reviewed and selected scientific outcome of the conference, which had the motto: "Better software = more efficient enterprise: challenges and solutions". Following this mission, this book is a compilation of challenges and needs of the industry, as well as research findings and achievements that could address the posed problems in software engineering. Some of these challenges included in the book are: increasing levels of abstraction for programming constructs, increasing levels of software reuse, increasing levels of automation, optimizing software development cycles. The book provides a platform for communication between researchers, young and established, and practitioners.
Requirements and Domain Modeling -- Quality Assurance -- Software Process Improvement.
Keywords: Computational intelligence; Software engineering; Artificial intelligence; Computational Intelligence; Software Engineering; Artificial Intelligence